Half-Sandwich Arene-Osmium(II) Complexes with Phosphinite Ligands - Rebeca González-Fernández (Molbank, 2020)
The synthesis of a series of arene-osmium(II) complexes containing phosphinite-type ligands, namely, [OsCl2(η6-p-cymene){R2PO(CH2)nPh}] (R = Ph, n = 1 (4a), 2 (4b), 3 (4c); R = iPr, n = 1 (5a), 2 (5b), 3 (5c)) and [OsCl2(η6-benzene){iPr2PO(CH2)2Ph}] (7), is presented. All these compounds were characterized by elemental analysis and multinuclear NMR spectroscopy (31P{1H}, 1H and 13C{1H}), and the structure of [OsCl2(η6-p-cymene){Ph2PO(CH2)3Ph}] (4c) unequivocally confirmed through a single-crystal X-ray diffraction study. Attempts to generate the tethered species [OsCl2{η6:κ1(P)-C6H5(CH2)nOPR2}] by intramolecular exchange of the coordinated arene in 4-5a-c or 7, upon thermal or MW heating, failed.